Vegetation and climate changes since the Last Glacial Maximum inferred from high-resolution pollen records from the Sichuan Basin, southwest China - Deng, Yunkai; Ma, Chunmei; Huang, Ming; Zhao, Lin; Shang, Guangchun; Tang, Lingyu; Lu, Huayu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
Reconstructing the vegetation history of southwest China since the Last Glacial Maximum is crucial for understanding the evolution of the Indian summer monsoon. In this study, we present a high-resolution palynological investigation from a 5 m core from the Ganchi peatland (southwest margin of the Sichuan Basin, southwest China) in order to reconstruct regional vegetation and climate over the last 25 kyrs. The succession, from bottom to top, comprises lake, wetland, and peat deposits, and wetland/aquatic pollen types are found to be a sensitive indicator of palaeoenvironmental change. Deciduous broad leaf forests dominated by Betula were present between 25-18 cal kyrs BP, suggesting a cold and dry climate during the Last Glacial Maximum. After 18 cal kyrs BP, temperature and summer insolation increased gradually, marking the Lateglacial transition. Thermophilous and hygrophilous species expanded between 11-8 cal kyrs BP, indicating a progressively warmer and wetter climate. From 8-4 cal kyrs BP, evergreen forests developed, while Tsuga reached its maxim abundance, implying a warm and humid climate coincided with the mid-Holocene climatic optimum. Results indicate that residual ice sheets may have impeded the northward shift of the Intertropical Convergence Zone, resulting in peak Holocene warmth lagging behind peak summer insolation forcing. Vegetation change was primarily controlled by climate, with no obvious evidence of anthropogenic disturbance until the last 1 cal kyrs BP. Our study shows that vegetation and climate in the southwest margin of the Sichuan Basin were controlled by summer insolation and ice sheet dynamics, and also influenced by sea surface temperature in the Indian Ocean.